Aberrant expansion of circulating CD4+CXCR5+CCR7loPD1hi Tfh precursor cells in idiopathic inflammatory myopathy. (27th December 2019) - Zhang, Lu; Li, Wenli; Cai, Ying; Liu, Xia; Peng, Qinglin; Liang, Lin
Abstract: Objective: To determine circulating follicular T helper (Tfh) cell precursor and its relationship with clinical characteristics in idiopathic inflammatory myopathy (IIM). Methods: The study population included 47 patients with IIM and 30 healthy controls. Circulating CD4 + CXCR5 + CCR7 lo PD‐1 hi T cells and intracellular interleukin (IL)‐21 were assessed by flow cytometry. Serum IL‐21 levels were measured by enzyme‐linked immunosorbent assay. The disease activity was evaluated using myositis disease activity assessment visual analog scales (VAS) as well as muscle and physician global assessment (PGA). Results: The percentage of the CCR7 lo PD‐1 hi subset cells within CD4 + CXCR5 + T cells was significantly increased in patients with IIM compared to that in healthy controls (14.3 ± 6.5 vs 11.4 ± 2.6, P  = .009). Patients with higher percentages of CCR7 lo PD‐1 hi subsets presented with higher PGA VAS ( P  = .000), muscle VAS ( P  = .000), as well as serum creatinine kinase (CK) levels ( P  = .000) than those with lower percentages of CCR7 lo PD‐1 hi subsets. IL‐21 expression significantly increased in CD4 + CXCR5 + CCR7 lo PD‐1 hi T cells in patients with IIM compared to that in healthy controls (26.07 ± 7.38 vs 19.25 ± 5.67, P  = .001). Meanwhile, both the CCR7 lo PD‐1 hi subset and intracellular IL‐21 expression in IIM patients showed significantly positive correlation with PGA VAS, muscle VAS and serum CK levels. Circulating CD4 + CXCR5 + CCR7 lo PD‐1 hi T cells and intracellular IL‐21 decreased significantly when disease was improved ( P  = .018; P  = .028). Conclusion: The percentage of circulating CCR7 lo PD‐1 hi subset among total CD4 + CXCR5 + T cells and intracellular IL‐21 expression expanded and showed significant correlation with disease activity in IIM. The circulating follicular helper T cell precursor may be involved in the pathogenesis, especially muscle injury in IIM.